Analysis of the Structure of Monopoly Markets and Their Impact on Consumer Well-Being: A Case Study on the National Electricity Industry - Kholilul Kholik; Risliana Octavia Siregar (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the structure of the monopoly market and its impact on consumer welfare in the national electricity industry. The research uses a qualitative approach with a case study method. Data was obtained through literature studies, official reports, and policy documents related to the electricity sector. The results of the study show that the structure of the monopoly market has a significant impact on prices, service quality, and the limitation of consumer choices. Although monopolies are natural, government policies play an important role in maintaining a balance between economic efficiency and consumer protection. This study recommends strengthening regulations, improving managerial efficiency, and continuous innovation to improve consumer welfare.